2022
DOI: 10.3390/chemengineering6060093
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Experiments on Pyrolysis of Walnut Shells Using a Fixed-Bed Reactor

Abstract: Pyrolysis is a low-emission and sustainable thermochemical technique used in the production of biofuels, which can be used as an alternative to fossil fuels. Understanding the kinetic characterization of biomass pyrolysis is essential for process upscaling and optimization. There is no accepted model that can predict pyrolysis kinetics over a wide range of pyrolysis conditions and biomass types. This study investigates whether or not the classical lumped kinetic model with a three-competitive reaction scheme c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The experimental data show that the solid yield drops monotonically with the maximum process temperature, while the tar and gas yields increase with the maximum process temperature for any experiments in the temperature range of 300−500 °C. 23,42 The modeling results from all three models confirmed that, with an increase of the maximum pyrolysis temperature, the final product volume of tar will increase at first and then reach an approximate plateau level for processes that peat at around 400−500 °C.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…The experimental data show that the solid yield drops monotonically with the maximum process temperature, while the tar and gas yields increase with the maximum process temperature for any experiments in the temperature range of 300−500 °C. 23,42 The modeling results from all three models confirmed that, with an increase of the maximum pyrolysis temperature, the final product volume of tar will increase at first and then reach an approximate plateau level for processes that peat at around 400−500 °C.…”
Section: Resultsmentioning
confidence: 77%
“…The results demonstrate that including secondary char reactions does not enhance the precision of predicting plastic pyrolysis products (at least for the PMMA-like polymer examined here) to the same extent as it did for biomass. The kinetic scheme of Model III most accurately predicts the decomposition of biomass pyrolysis. , Compared to the biomass pyrolysis modeling previously investigated by the authors, , the behavior of plastic pyrolysis is different. The results here suggest that, in plastic pyrolysis, there is the presence of secondary tar reactions, whereas primary char once formed subsequently acts as an inert substance.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations